Structural reliability study of hydrokinetic turbine blade operating in tropical conditions - Rajaram, Attukur Nandagopal (Nanyang Technological University, 2020)
The present research work covers the hydrodynamic and the structural designing of a horizontal axis tidal turbine (HATT) blade. The first part of the work investigates the possible hydrodynamic design improvements of a HATT blade that operates in the tropical conditions. The structural analysis of the blade is performed in the second part by considering the seawater induced degradation of the blade material. In tropical conditions, the tidal flow speed is low, which reduces the hydrodynamic capacity of the HATT blade. One way to improve the hydrodynamic efficiency of the blade is to select an efficient 2D cross-section (hydrofoil) of the blade, for a given flow condition. In the current work, a base hydrofoil geometry is optimised to obtain a new hydrofoil that has superior characteristics for the given flow conditions. Maximising the lift-to-drag ratio and the lift coefficient of the hydrofoil was set as objectives (non-conflicting) while avoiding cavitation during the turbine operation was one of the constraints. The multi-objective optimization problem was setup and solved using the OpenMDAO and the NSGAII, respectively, to generate four optimised hydrofoils. The Harp_opt software was used to design a 0.5m blade using the optimised hydrofoils which exhibited better performance than another 0.5m blade designed using the state-of-the-art NREL hydrofoils as the 2D sections. The carbon fibre reinforced polymer (CFRP) material was chosen as the blade material for its high specific strength, corrosion resistance and design flexibility. The seawater induced degradation of the CFRP material was quantified by investigating the hygrothermal ageing behaviour of the material. The moisture diffusion into the material was modelled using the Fick and the Langmuir models. Further, the degradation of the quasi-static and fatigue properties of the material coupons due to the hygrothermal ageing was studied in detail. The quasi-static tensile, compressive and flexure properties were experimentally determined as a function of the absorbed moisture content, and an empirical model was adopted from the literature to fit the experimental data. The statistical distribution of the material static strength at different moisture content was established using the Weibull statistics, and its parameters were derived as a function of the empirical model parameters and the absorbed moisture content. The flexure fatigue properties of the material with two layup sequences, custom-named as the unconstrained laminate [06], and constrained laminate [±45/03]S was compared to investigate the ‘constraining effect’ on the zero-degree plies (imposed by the ±45 plies) of the constrained laminate. The comparison was made in terms of the synergetic effect of the stress ratio and ageing on the fatigue response of the constrained and unconstrained laminate. The constraining effect had a considerable impact on the static flexure behaviour of the dry constrained laminate, and it also significantly deteriorated its low stress ratio fatigue behaviour due to stress concentration. However, the high stress ratio fatigue behaviour of the constrained laminate was better in the dry condition which later deteriorated due to ageing. A probabilistic approach was followed to compare the static flapwise bending performance of the 0.5m blade under the dry and the hygrothermal aged material conditions. The effect of the uncertainties in the material properties and the blade static loading on the static structural response of the blade were investigated. The polynomial chaos expansion method was used to build a surrogate model for the blade static flapwise bending analysis, and later in combination with the Monte-Carlo method, the statistical distribution of the structural responses of the blade was estimated. Using the Tsai-Wu failure index, the failure probability of the blade was shown to increase due to the ageing induced material degradation. The effect of the asymmetric moisture diffusion through the thickness of a laminate on the material properties of the plies was also investigated. The moisture induced material property asymmetry in the laminate resulted in bending-extension coupling due to the applied bending moment. The stress along the laminate thickness was also affected due to the asymmetry.